Comparisons between processing linguistic and mathematical negations from the perspective of the practice effect and working memory - Hikari Kinjo; Toshiki Saito (Language and Cognition)
A negated proposition can be expressed linguistically and mathematically. The current study examined the one-step and two-step procedure accounts from the perspective of the practice effect and working memory by comparing performance in two simple linguistic and mathematical verification tasks. Two online experiments were conducted with simple verification tasks over 10 practice sessions: a figure-equation task (e.g., ● ≠ ▲) and a figure-sentence task (e.g., ● is not ▲). Although reaction times in the equation task were faster than in the sentence task, both tasks showed that reaction times in negations took longer than those in affirmations regardless of the sameness of the figures in the target propositions (i.e., TA < FN and FA < TN) in both experiments, and the trend was not changed by the practice. The similar trends across the tasks, regardless of the practice, support the two-step procedure account, in which participants first evaluate the positive argument of negation and then reverse the response in negative propositions. Furthermore, high correlations between performance in the tasks and both verbal and spatial working memory tasks suggest that verification judgments may involve not only language processing but also more general cognitive processing.